A study of comparison of efficacy and side effects of intravenous paracetamol and intravenous diclofenac as a postoperative analgesic - Agrawal, Sharda A.; Nikhate, Surendra D.; Thakur, Manasi M.; Bal, Himadri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
B Background: A postoperative patient suffers from pain the best relief of which is a clinician’s duty. Till date very few studies have been conducted for comparison of paracetamol and diclofenac as analgesics. As a result a comparative study between Paracetamol and Diclofenac was carried out. The aim of the study was to compare the efficacy and side effects of intravenous Paracetamol and intravenous Diclofenac in patients undergoing major abdominal open surgeries in obstetrics and gynaecology. The study was conducted to assess the postoperative visual analogue pain scores (VAS) and total analgesic requirement in the first 24 hours and also to study the total requirement of additional analgesics despite administration of either Paracetamol or Diclofenac in postoperative period. Methods: 100 patients satisfying the inclusion/exclusion criteria were recruited for the study. They were divided into two groups of 50 each. Group A was given IV Paracetamol 6 hourly for 48 hours starting 2 hours after surgery. Group B was given IV Diclofenac 8 hourly for 48 hours starting 2 hours after surgery. Patients were assessed for pain relief by visual analogue scale (VAS) of zero to ten after 6 hours, 12 hours, 24 hours and 48 hours of surgery by asking the patient to point the position on the 100 mm scale. Results: The results revealed that when we compared the VAS scores between the 2 Groups at different time intervals, it showed that at 24 hours and 48 hours VAS score in the Diclofenac Group was significantly less than the Paracetamol Group. The main side effects were nausea and vomiting in both the groups. There was more nausea and vomiting in Diclofenac group compared to Paracetamol group. Conclusions: It was concluded that at 24 hour and 48 hour pain reduction was more in the Diclofenac group as compared to Paracetamol group, but the side effects were more in the Diclofenac group compared to Paracetamol group.